2000
DOI: 10.2337/diacare.23.8.1108
|View full text |Cite
|
Sign up to set email alerts
|

The 1997 American Diabetes Association and 1999 World Health Organization criteria for hyperglycemia in the diagnosis and prediction of diabetes.

Abstract: RESEARCH DESIGN AND METHODS -The frequencies of diabetes by the 3 sets of criteria were compared in 5,023 adult Pima Indians not taking hypoglycemic drugs. Among nondiabetic subjects, fasting plasma glucose (FPG) and 2-h postload plasma glucose (2-h PG) concentrations and categories of impaired glucose regulation or diabetes were evaluated as predictors of diabetes defined by 1999 WHO criteria.RESULTS -The frequency of diabetes was 12.5% by 1997 ADA criteria, 14.6% by 1985 WHO criteria, and 15.3% by 1999 WHO c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
307
3
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(342 citation statements)
references
References 12 publications
20
307
3
7
Order By: Relevance
“…These results underscore the urgency for development of national strategies, which must cover both urban and rural communities, to improve detection, prevention and treatment of diabetes in China in order to avert an epidemic of diabetes and its complications. dicate that impaired fasting glucose might not be as sensitive as impaired glucose tolerance as a predictor of diabetes [22,23]. Furthermore, the ADA and WHO criteria might identify different groups of individuals [24,25].…”
Section: Mean Glucose Concentrationsmentioning
confidence: 99%
“…These results underscore the urgency for development of national strategies, which must cover both urban and rural communities, to improve detection, prevention and treatment of diabetes in China in order to avert an epidemic of diabetes and its complications. dicate that impaired fasting glucose might not be as sensitive as impaired glucose tolerance as a predictor of diabetes [22,23]. Furthermore, the ADA and WHO criteria might identify different groups of individuals [24,25].…”
Section: Mean Glucose Concentrationsmentioning
confidence: 99%
“…The sensitivity and specificity of IFG and IGT in predicting subsequent development of diabetes are important characteristics of the two glucose categories. Previous studies have shown that in a high-risk population (Pima Indians) the sensitivity of the IFG category is lower than that of the IGT category [20], while in the European, white Caucasian population the sensitivity was the same for IFG and IGT [21]. The difference in performance between IFG and IGT may reflect the fact that the WHO-defined IFG group only identifies 20 to 30% of all individuals with IGT.…”
Section: Discussionmentioning
confidence: 95%
“…It became clear that these two categories did not identify the same individuals [11] and they did not have the same impact on morbidity, mortality and cardiovascular risk profile [6,12]. However, both IFG and IGT do predict subsequent development of diabetes [20,21], confirming their role as pre-diabetic states. In the present study we have reviewed the impact of the ADA's proposed change in diagnostic criteria for IFG with respect to the prevalence of IFG, the concordance between IFG and IGT, the cardiovascular risk profiles and the likely impact on prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension was defined as a prior history of hypertension, current antihypertensive medication or a systolic and diastolic blood pressure of ≥140 and ≥90 mmHg respectively at discharge. Diabetes was considered to be present if a patient had a history of diabetes and glucose-lowering medication before admission, and also if the fasting glucose level was ≥7.0 mmol/l (126 mg/dl) during hospitalisation [7]. ICH volumes were measured using an image analyser (Image-Pro Plus; Media Cybernetics, Silver Spring, MD, USA).…”
Section: Methodsmentioning
confidence: 99%